Popularity and Common Issues of Teaching Sports Games at Elementary Schools in Slovakia - Miroslav Nemec; Štefan Adamčák; Michal Marko (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2022)
Within the article, we analyze and evaluate the popularity and common issues of teaching sports games in physical and sport education at elementary schools in Slovakia. A survey was the research instrument for collecting the primary data, aimed at male (620) and female (506) teachers of physical and sport education at the second elementary education stage of three regions of Slovakia. Detecting of teachers' perception was surveyed in period of three years (2017 - 2020). Each answer of male and female teachers was compared and evaluated by using the chi-square test (X2), while the significance level (α) was .01 and .05. In general, the sports games were the most popular activities among the male and female teachers of physical and sport education (58.02 %; n = 653). More than 41 % of male and female teachers' answers about the most significant factors influencing the quality of teaching sports games were spatial and material conditions. The reason for that was partly due to the low time allowance of teaching sports games (28.86 %; n = 152). The traditional sports games (football, volleyball, basketball) were the best secured, in terms of material conditions, in contrast to floorball (34,70 %; n = 390).